Comparison of Wolbachia Bacterial Density in Females of Four Thelythokous Strains of Trichogramma cordubensis and T. evanescens (Hymenoptera, Trichogrammatidae) - Pascal, C.; Pintureau, B.; Katchadourian, C.; Grenier, S.; Bolland, P.; Robin, C.; Vallier, A. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2006)
The endosymbionts of the genus Wolbachia
infect numerous arthropods and nematods, and often cause different effects on the reproduction of
these hosts. The endosymbiotic bacteria Wolbachia induces the thelytokous mode of reproduction in
the egg parasitoids of the genus Trichogramma. The Dot-blot technique was performed to compare the
symbiont Wolbachia density using the wsp gene of Wolbachia and the 18S gene of Trichogramma. It was
established that Wolbachia density is not different in two host species, Trichogramma cordubensis Vargas
et Cabello and T. evanescens Haliday. Эндосимбиотические бактерии рода Wolbachia заражают различных артропод и нематод, оказывая различный эффект на их репродуктивные особенности. Бактерии рода Wolbachia вызывают телитокию у яйцеедов рода Trichogramma. Использована техника Dot-blot для сравнения плотности симбионта Wolbachia, с помощью выделения гена wsp у симбионта Wolbachia и гена 18S у Trichogramma. Экспериментально установлено, что плотность Wolbachia у двух видов, Trichogramma cordubensis Vargas et Cabello и T. evanescens Haliday, одинаковая.